Physical Education Activities in Sports Schools - Hamrokulov Rasuljon; Komilov Talibjon (Genius Journals, 2023)
In this article, the description, structure, and stages of the work of children's sports schools are described in detail. Sports schools specializing in the preparation of Olympic reserves for children and teenagers are separate or equipped with a sports base and highly qualified coaches-teachers. organization under schools is justified
Keywords: Children's sports school; sports training; preparatory and initial and other training groups; highly qualified trainers-teachers